Oral pregnancy tumor - Shailesh M Gondivkar; Amol Gadbail; Revant Chole (Wolters Kluwer Medknow Publications, 2010)
Pyogenic granuloma is one of the inflammatory hyperplasias seen in the oral cavity. This term is a misnomer because the lesion is unrelated to infection and in reality arises in response to various stimuli such as low-grade local irritation, traumatic injury, or hormonal factors. It predominantly occurs in the second decade of life in young females, possibly because of the vascular effects of female hormones. Clinically, oral pyogenic granuloma is a smooth or lobulated exophytic lesion manifesting as small, red erythematous growth on a pedunculated or sometimes sessile base, which is usually hemorrhagic. Although excisional surgery is the treatment of choice , some other treatment protocols such as the use of Nd:YAG laser, flash lamp pulsed dye laser, cryosurgery, intralesional injection of ethanol or corticosteroids, and sodium tetradecyl sulfate sclerotherapy have been proposed. We present the case of a 25-year-old pregnant woman with large oral pyogenic granuloma.